DEVELOPING STUDENTS’ CRITICAL THINKING THROUGH READING-BASED LITERACY ACTIVITIES IN SECONDARY EFL CLASSROOMS: AN INTERVENTION STUDY - Fitriani Fitriani; Fitriah Hayati (Sensei International Journal of Education and Linguistic, 2023)
Critical thinking is an essential competence in language education because students are expected not only to understand texts but also to interpret information, evaluate arguments, identify assumptions, make inferences, and justify their opinions using textual evidence. However, reading instruction in many English as a foreign language classrooms still emphasizes literal comprehension, vocabulary translation, and answer-finding activities. This study aims to examine the effectiveness of reading-based literacy activities in developing students’ critical thinking and to explore how students experience critical reading tasks in secondary EFL classrooms. The study employed a mixed-method design using a quasi-experimental pretest-posttest control group approach supported by classroom observations, student interviews, reflective journals, and document analysis. The participants were 74 Grade VIII students divided into an experimental group and a control group. The experimental group received reading-based literacy activities involving prediction, questioning, evidence mapping, inference-making, argument evaluation, perspective comparison, and reflective response writing. The control group received conventional reading instruction. Quantitative data were analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, normalized gain scores, and effect size analysis. Qualitative data were analyzed thematically. The findings showed that the experimental group achieved significantly higher critical thinking improvement than the control group. Qualitative findings revealed that reading-based literacy activities strengthened students’ ability to question texts, locate evidence, compare viewpoints, infer implicit meanings, and justify interpretations. The study concludes that reading-based literacy activities can develop students’ critical thinking when they are explicit, evidence-based, dialogic, and supported by reflective assessment.